Systematic study of the genera Phryno Robineau-Desvoidy and Botria Rondani in the Palearctic Region, with discussions of their phylogenetic positions (Diptera, Tachinidae) - Tachi, Takuji (Zootaxa, 2013)
Six species of Phryno Robineau-Desvoidy and three species of Botria Rondani are revised, including four new species: P. brevicornis sp. nov., P. koreana sp. nov., P. nepalensis sp. nov. and P. tenuiforceps sp. nov. A key to the species of these genera is provided. A phylogenetic analysis was performed using morphological characters to investigate the placement of genera in the Zenillia group (sensu Tschorsnig 1985). The inferred trees indicate that Phryno is closely related to Botria, but monophyly of Phryno is unclear. Based on the results of the analysis, the Zenillia group is redefined to include Allo-phorocera Hendel, Botria, Ceromasia Rondani, Calozenillia Townsend (new placement), Cyzenis Robineau-Desvoidy, Erycilla Mesnil, Phryno, Rhacodinella Mesnil, Sericozenillia Mesnil (new placement) and Zenillia Robineau-Desvoidy.